Acute Kidney Injury in Patients Using Polyethylene Glycol as Bowel Cleansing Agent for Colonoscopy - Chhetri, Gaurav; Baral, Anil; Hada, Rajani; Sedhain, Arun; Khatri, Bikash; Dahal, Kashyap; Piya, Albina; Singh, Anurag Prasad; Basnet, Bhupendra Kumar (Nepalese Medical Journal, 2022)
Introduction: The use of polyethylene glycol-based solutions is the gold standard for bowel preparation for colonoscopy. However, polyethylene glycol use might be associated with the risk of acute kidney injury. We aim to find out acute kidney injury and risk factors associated with the development of acute kidney injury in patients using polyethylene glycol for colonoscopy. Materials and Methods: This was an observational study conducted in the Department of Nephrology and Gastroenterology, Bir hospital. Patients who underwent colonoscopy using polyethylene glycol were included in the study and assessed for acute kidney injury; its incidence, association of risk factors with acute kidney injury, and outcome (complete recovery or no recovery) of acute kidney injury by 3 months. Results: The mean age of the patients was 45.81 ± 18.60 years with the majority of the patients being male (60%). Out of 48 study participants, 4(8%) develop acute kidney injury. Multivariate regression analysis depicted that chronic kidney disease, chronic liver disease, congestive cardiac failure, and use of non-steroidal anti-inflammatory drugs, angiotensin receptor blockers, and diuretics drugs were the predictors which significantly influenced the occurrence of acute kidney injury in patients using polyethylene glycol. Conclusions: The evidence strongly suggests that in patients without preexisting renal disease, comorbidities, or use of drugs; the risk of renal impairment is low after colonoscopy using polyethylene glycol as a bowel cleansing agent. In the presence of risk factors for renal dysfunction, polyethylene glycol should be used cautiously.